2021
DOI: 10.1364/ol.414392
|View full text |Cite
|
Sign up to set email alerts
|

Highly resistant all-silica polarizing coatings for normal incidence applications

Abstract: Several fundamental restrictions limit the implementation of microlasers in high power systems, low resistivity of coatings and compactness of elements, especially if control of polarization is necessary. Thin-film-based coatings with extremely high optical resistivity and polarizing properties for normal incidence could become a preferable solution. In this Letter, a novel multilayer approach to form all-silica polarizing coatings for normal incidence angle applications is proposed. Laser induced damage thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…[19,20] Additionally, using glancing angle deposition (GLAD) method enabled to form optical components for high power laser systems due to enhanced anisotropy in silica thin films. [21][22][23] Optical properties of such coatings strongly depend on deposition conditions and features of the substrate. [24,25] Therefore, flexible and high resolution method for anisotropy analysis is essential for further development of complex elements.…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] Additionally, using glancing angle deposition (GLAD) method enabled to form optical components for high power laser systems due to enhanced anisotropy in silica thin films. [21][22][23] Optical properties of such coatings strongly depend on deposition conditions and features of the substrate. [24,25] Therefore, flexible and high resolution method for anisotropy analysis is essential for further development of complex elements.…”
Section: Introductionmentioning
confidence: 99%
“…Tolenis et al group already demonstrated the possibility to create nano-structured films, which are capable to withstand up to 60 J/cm 2 at 355 nm wavelength ns pulses [5], however, the main limitation includes high number of defects. Over the past five years, glancing angle deposition (GLAD) method was improved in terms of different types of optical elements formation, such as antireflection [6], polarizing coatings [7] and already mentioned highly reflective components [5], where all of these papers report extremely high LIDT values compared with other technologies in ns regime. Although the main problems still remain -defects, which is difficult to eliminate.…”
Section: Introductionmentioning
confidence: 99%
“…Glancing angle deposition (GLAD) [1] can be used to make highly anisotropic thin films for light polarisation control, namely waveplates suited for the linear and circular polarisations [2,3] and polarisers for zero angle of incidence [4], by utilising complex arrangements of sample's tilt and rotation [5]. It becomes possible to make strongly birefringent thin films by GLAD using optically isotropic Si and SiO 2 materials [6].…”
Section: Introductionmentioning
confidence: 99%
“…Anisotropic Si has shown birefringence up to 0.25 in the IR spectral range (∼1500 nm) [15], while it was lower for silica; however, an augmented optical damage threshold was found in the case of silica in the UV-VIS range [3]. In both cases, the refractive index anisotropy of a film was created from an amorphous (isotropic) material, which can be applied on virtually any surface, including glass substrates [4] or laser crystals [16]. Such films are promising for development of micro-laser systems.…”
Section: Introductionmentioning
confidence: 99%